SATISFACCION DE LOS USUARIOS DEL CENTRO DE SALUD "A" VINCES (IESS - Cervantes Izquierdo, Roberta Abigail (2018)
408/5000 The present investigation is related to the analysis of the satisfaction of the affiliates who daily come to receive medical attention in the Health Center "A" Vinces, determining what are the causes and the effects that provoke that the patients present complaints and for If they are dissatisfied, the study will be carried out under the research line of the Administrative management model.